The effect of teacher empowerment-based course program on teachers' knowledge of Pancasila character on the Indonesia-Malaysia literacy - Daya Negri Wijaya; Evania Yafie; H. Hariyono; Andhika Yudha Pratama; Alfi Rohmatul Azizah; Suti Mega Nur Azizah (Universitas Muhammadiyah Malang, 2024)
The lack of teachers' ability to apply the Pancasila character can contribute to the fading of Pancasila culture abroad, especially for the families of Indonesian Immigrant Workers in Malaysia. This research aims to explore the understanding of the character of Pancasila among parents in the Indonesian-Malaysian literacy context. A quantitative research approach was used with a sample of 80 educators from the Kuala Lumpur Indonesian School and learning centers in Malaysia. The research instrument consists of a questionnaire with 15 items for the Teacher Empowerment Program variable and 14 items for Teacher Knowledge. Data analysis uses simple linear regression with validity, reliability, normality, heteroscedasticity, t test, and coefficient tests, which are processed using SPSS software. The research results found that the training program had a positive effect on teachers' knowledge about the character of Pancasila. The Teacher Empowerment Based Course Program has had a significant impact on teachers' understanding of the Indonesian-Malaysian Literacy Based Pancasila Character. After attending a course based on teacher empowerment, there was a significant increase in teachers' knowledge about the character of Pancasila based on Indonesian-Malaysian language literacy. This teacher empowerment-based course program provides educators with the opportunity to gain knowledge about Indonesian-Malaysian literacy. They can apply this knowledge through innovative and effective teaching methods. Future research could investigate further potential benefits beyond increasing teachers' knowledge after participating in this program.